GROWTH AND EXPRESSION PATTERN OF GROWTH-RELATED GENES IN THE FAST-GROWING GIANT GOURAMI Osphronemus goramy - Siska Aliyas Sandra; Hasan Nasrullah; Harton Arfah; Muhammad Zairin Jr.; Alimuddin Alimuddin (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2021)
Growth improvement of the giant gourami through molecular assisted selection offers a breakthrough solution regarding the slow growth problem in culturing the fish species. However, gene molecular expression studies and gene mapping information are scarce for this species. This study aimed to evaluate the growth, expression of the growth-related genes and compare the gene expressions between fast-growing (FG) and slow-growing (SG) fish. The polymorphism screenings were also conducted within the GH sequence of the FG and SG populations. Fish growth was analyzed by measuring length and weight once a month. The expression levels of GH, IGF1, AMPK, ARS-I, ALT, and AST genes were analyzed using real-time PCR. Twenty-five days old fish were reared for 30 days. The fish were continuously reared separately based on their body weight (BW) for 85 days until reaching 140 days old. At the end of the rearing period, the BW growth rate of the FG population was 1.569-fold higher, and body length (BL) growth was 1.056-fold higher than the SG population. FG fish have higher gene expression than the SG fish, indicating the important role of gene expression in fish growth. The polymorphisms screening within the GH sequences showed no significant difference between FG and SG fish of giant gourami. These research results provide valuable information in developing the marker-assisted selection for growth traits in giant gourami.